2002
DOI: 10.1128/jvi.76.15.7587-7594.2002
|View full text |Cite
|
Sign up to set email alerts
|

Shedding and Intracage Transmission of Sin Nombre Hantavirus in the Deer Mouse ( Peromyscus maniculatus ) Model

Abstract: The mechanism(s) by which Sin Nombre (SN) hantavirus is maintained in deer mouse populations is unclear. Field studies indicate that transmission occurs primarily if not exclusively via a horizontal mechanism. Using an experimental deer mouse infection model in an outdoor laboratory, we tested whether infected rodents shed SN virus in urine, feces, and saliva, whether infected mice transmit infection to naïve cage mates, and whether infected dams are able to vertically transmit virus or antibody to offspring. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
114
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(121 citation statements)
references
References 39 publications
4
114
0
3
Order By: Relevance
“…These results are concordant with findings by Botten et al (2000), who also found this stage of infection to be transient or rarely detected. Netski et al (1999) found that SNV antigen concentrations were highest in the kidneys of wild-caught deer mice that had no antibody to SNV but had SNV RNA in the blood (those that they presumed to have been infected very recently).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are concordant with findings by Botten et al (2000), who also found this stage of infection to be transient or rarely detected. Netski et al (1999) found that SNV antigen concentrations were highest in the kidneys of wild-caught deer mice that had no antibody to SNV but had SNV RNA in the blood (those that they presumed to have been infected very recently).…”
Section: Discussionsupporting
confidence: 92%
“…Other studies suggest that hantaviral replication in tissues is variable during chronic infection; intervals of virus shedding in urine, feces, and saliva and intermittent presence of viral RNA or even infectious virus in blood can be expected (Hutchinson et al, 1998;Botten et al, 2002). A second possible explanation for the alternating nature of viral RNA is viral recrudescence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prevalence of anti-SNV IgG in wild deer mice is highest in those Ͻ10.9 g mass, declines in mice Ն10.9-Յ14.3 g, and increases in those Ͼ14.3 g. The group of small mice probably acquired anti-SNV antibodies passively through the placenta and the decline in seroprevalence between birth and 14.3 g is thought to be due to attrition of maternal antibodies (Mills et al, 1997). Additional experimental evidence has continued to accrue demonstrating that specific anti-hantavirus IgG antibodies can be passed through the placenta and may be protective from challenge by SNV (Borucki et al, 2000;Camaioni, 2001;Botten et al, 2002).…”
Section: Discussionmentioning
confidence: 99%